Kepercayaan Konsumen Sebagai Mediator antara Promosi, Cash On Delivery, dan Keputusan Pembelian Online Produk Kecantikan Lokal - Tsalis Kurniawan Husain; Farizah Dhaifina Amran; Mais Ilsan; Laili Aqila; Indri Amelia (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2026)
In the competitive e-commerce landscape, local brands like Mabello Indonesia utilize promotions and Cash on Delivery (COD) to drive sales. This study examines the influence of these factors on purchasing decisions through consumer trust, focusing on local beauty products in Makassar, Indonesia. Using a quantitative SEM-PLS (Structural Equation Modeling–Partial Least Squares) approach, data were collected from 100 young e-commerce users. Results: Promotions significantly influence purchasing decisions, with consumer trust acting as a significant mediator. However, consumer trust does not significantly mediate the relationship between COD and purchasing decisions. This suggests that for digital-native consumers, COD has shifted from a risk-mitigation tool to a mere logistical convenience. Practical Implications: Local MSMEs should prioritize authentic, culturally grounded promotions to foster long-term trust while maintaining COD services to ensure transaction certainty.